A Comparative Study of the Implementation of 4G and 5G Networks in IIoT Process Automation Systems - Wardana, Awang Noor Indra; Putra, Iqbal Aliandra; Muhammad, Fawwaz Afif (Universitas Syiah Kuala, 2025)
The industrial internet-of-things (IIoT) has recently become an important requirement in the process industry. The factories must be able to integrate process automation devices such as programmable logic controllers and industrial computers with mobile devices, especially to support their maintenance and operations. Connectivity with mobile devices has the consequence that cellular networks must be specified to the needs of the industry itself. Comparative studies on using cellular networks in process automation systems are urgently needed. The research that has been conducted is a comparative study between the use of 4G and 5G cellular networks in IIoT process automation systems. It can be seen in the result that the 4G cellular network is sufficient to be used for industries that require mobile devices for monitoring functions, as seen from the results showing the latency obtained is 17.03 ms, jitter is 9.5 ms, packet loss is 6.67 %, and throughput is 192.73 Kbps. However, for the industry that needs to perform real-time control, mobile connectivity has to use a 5G network with better performance metrics with a latency of 15.21 ms, jitter of 5.43 ms, packet loss of 2.67 %, and throughput of 217.19 Kbps. The research results are needed by the process industry in Indonesia, which is widely spread on the island as an archipelago with quite varied cellular network connectivity quality.